Tendencies in political behavior of men and women – a study on the behavior of Vietnamese political elites toward their promotion opportunities (Revista de Investigaciones Universidad del Quindío, 2021)
Purpose of the study: This paper aims to explore some of the crucial reasons limiting the contemporary participation of Vietnamese women in political leadership by reviewing the attitudes of male and female political elites toward opportunities for political promotionMethodology: The population of this research is the leaders and potential leaders of the Vietnamese political system. The purposive sampling method was used, resulting in 324 respondents. In addition, in-depth interviews were conducted with 21 government officials. Quantitative data resulting from questionnaires were processed using the Statistical Package for the Social Sciences (SPSS) software for Windows, version 19. Qualitative data were processed manually. No discussion or explanation.Main Findings: The study results show that the majority of Vietnamese political elites are willing to take up opportunities for promotion. However, women's readiness to accept opportunities for promotion is often lower than that of men, due to social expectations on their traditional gender roles. Besides, improper legal frameworks and policies significantly contribute to women having less political ambition and giving up on their dreams earlier than their male counterparts.Applications of this study: The results of this study are useful for the Vietnamese Government to develop measures for removing the obstacles that hinder women’s political participation.Novelty/Originality of this study: This study uses data from the author’s original survey.
Keywords: political behavior; promotion opportunities; ellites; gender role; retirement age